2011
DOI: 10.1007/s10661-011-2459-y
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and fate of steroid estrogens in the largest wastewater treatment plant in Beijing, China

Abstract: Concern over steroid estrogens has increased rapidly in recent years due to their adverse health effects. Effluent discharge from wastewater treatment plants (WWTPs) is the main pollutant source for environmental water. To understand the pollutant level and fate of steroid estrogens in WWTPs, the occurrence of estrone (E1), 17-β-estradiol (E2), estriol (E3), and 17-β-ethinylestradiol (EE2) was investigated in the Gaobeidian WWTP in Beijing, China. Water samples from influent as well as effluent from second sed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(27 citation statements)
references
References 58 publications
2
24
1
Order By: Relevance
“…Exogenous steroid chemicals are widely detected in a number of water systems, ranging from several to hundreds ng/L (Backe et al, 2011;Chang et al, 2011;Jiang et al, 2012;Zhou et al, 2012). These compounds produce detrimental biological effects even at low ng/L levels (Filby et al, 2007;Leet et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Exogenous steroid chemicals are widely detected in a number of water systems, ranging from several to hundreds ng/L (Backe et al, 2011;Chang et al, 2011;Jiang et al, 2012;Zhou et al, 2012). These compounds produce detrimental biological effects even at low ng/L levels (Filby et al, 2007;Leet et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Estrogenic chemicals, such as estrone (E1), 17b-estradiol (E2), estriol (E3) and 17a-ethinylestradiol (EE2) and androgenic chemicals, such as methyltestosterone, testosterone, and androstenedione have been detected in a number of water systems at concentration levels between 1 and 100 ng/L (Backe et al, 2011;Chang et al, 2011;Jiang et al, 2012;Zhou et al, 2012). Even at low ng/L, these exogenous steroid chemicals have the potential to produce detrimental biological effects.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the widespread application of PAEs, they are the most abundant compounds in aquatic environmental matrices in China (Cai et al 2007). High levels of DBP and other PAEs have been reported in water samples (ng/L to mg/L range) in recent years (Li et al 2010b;Shi et al 2012;Zhou & Liu 2013). Zheng et al (2014) reported that PAEs in Guanting Reservoir might come from municipal sewage and domestic waste and might be influenced by anthropogenic daily activities.…”
Section: Discussionmentioning
confidence: 99%
“…17α-Ethinylestradiol (EE2), a synthetic estrogen that is commonly used as a contraceptive and hormone replacement (Zhou et al, 2012), and other medicinal compounds reach water bodies via urine, feces or manure (Halling-Sorensen et al, 1998). King et al (2016) reported that the concentration of EE2 in Australian wastewater was 0.1 to 0.5 ngL -1 .…”
Section: Introductionmentioning
confidence: 99%